ASUHAN KEPERAWATAN PADA PASIEN SKIZOFRENIA DENGAN MASALAH KEPERAWATAN HARGA DIRI RENDAH KRONIS DI RUANG SENA RUMAH SAKIT JIWA DAERAH DR. ARIF ZAINUDIN SURAKARTA - Handa Tri Nurcahyo; Ririn Nasriati; Filia Icha Sukamto (Health Sciences Journal, 2022)
AbstractLow self-esteem is one of the nursing problems in mental nursing that can leod to health disorders such as social interaction disorder. The purpos of this paper is to provide nursing care to schizophrenic clients with chronic low self-esteem problems, including assessment, data analysis, diagnosis, intervention, implementation, and evaluation of nursing.Nursing care was conducted in the sena room of Rumah Sakit Jiwa Daerah Dr. Arif Zainudin Surakarta for four days on 02 February to 05 February. The methode used in thiis scientific paper is the approach method of the nursing process.From the results of the study, it was found that the client experienced auditory hallucination. After the implementation of nursing using the implementationi strategy, on the 1st implementation strategy the client is able to choose the activities that can be done, the client chooses the activity of tidy up the bed, tappingthe plate, sweeping, and reading a short letter. On the 2 implementation strategy clients conduct training activities above Together with nurses and put it into the schedule of clients are able to do activities that are arranged and planned to include them i theschedule. Clients with chronically low self-esteem need a friend in interacting and nurses should use good communication. The role of nurses is very important in providing nursing care. This helps in the client's recovery process.